‘Beyond broken bones’: the hidden impact of depression on orthopaedic patients-the silent struggle - Ganesh, Arjun; Kumar, M. Mohan (International Journal of Research in Orthopaedics, 2023)
The recognition of the interplay between physical and mental health is of increasing importance in the management of orthopaedic patients. Orthopaedic patients not only encounter physical impairments but also mental health complications such as anxiety and depression. While orthopaedic surgeons traditionally focus on the physical aspects of patients' recovery, recent studies have highlighted the significant impact of psychological factors on functional outcomes and quality of life; thus, necessitating a comprehensive treatment approach.